The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1053/j.oto.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tendon Stem/Progenitor Cells and Platelet-Rich Plasma to Treat Tendon Injuries

Abstract: Tendon injuries like tendinopathy are a serious healthcare problem in the United States. However, current treatments for tendon injuries are largely palliative. Biologics treatments, including tendon stem/progenitor cells (TSCs) and platelet rich plasma (PRP) hold great potential to effectively treat tendon injuries. TSCs are tendon specific stem cells and have the ability to differentiate into tenocytes, the resident tendon cells responsible for tendon homeostasis and tendon repair in case of an injury. TSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 65 publications
(72 reference statements)
3
23
0
2
Order By: Relevance
“…Collectively, these two stem cell types have been differentiated into almost every connective tissue lineage, including bone, cartilage, tendon, and the intervertebral disk . More recently, cells with self‐renewal capacity, clonogenicity, and multilineage potential have been isolated from tendon tissue . In the original characterization of these tendon stem/progenitor cells (TSPCs), it was suggested that these cells may reside within the tendon proper and comprise a subpopulation of tenocytes .…”
Section: Stem Cell‐based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these two stem cell types have been differentiated into almost every connective tissue lineage, including bone, cartilage, tendon, and the intervertebral disk . More recently, cells with self‐renewal capacity, clonogenicity, and multilineage potential have been isolated from tendon tissue . In the original characterization of these tendon stem/progenitor cells (TSPCs), it was suggested that these cells may reside within the tendon proper and comprise a subpopulation of tenocytes .…”
Section: Stem Cell‐based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
“…[97][98][99][100][101] More recently, cells with self-renewal capacity, clonogenicity, and multilineage potential have been isolated from tendon tissue. [102][103][104][105][106] In the original characterization of these tendon stem/progenitor cells (TSPCs), it was suggested that these cells may reside within the tendon proper and comprise a subpopulation of tenocytes. 102 Other studies, however, suggest that TSPCs may be located within the epitenon, which is the thin epithelial layer surrounding all tendons.…”
Section: Stem Cell-based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
“…8.3) [59]. Clinical trials have studied the effects of PRP injection as a primary treatment or augmentation of current therapies for patellar tendinopathy, Achilles tendinosis, and lateral epicondylitis [60].…”
Section: Tendinopathymentioning
confidence: 99%
“…MSCs hold promise in the use of tendinopathy [60]. As ongoing and future research advances our understanding of tendinopathy basic science, the role of angiogenesis in tendon healing, and the link between histology and clinical findings, the use of MSCs will likely continue to play an increasing role in treatment of this common yet often recalcitrant pathology.…”
Section: Future Directionsmentioning
confidence: 99%
“…This therapy is widely experimented in different fields of medicine to test its potential role to enhance tissue re-generation [13][14][15][16][17]. In a recent non-controlled prospective trial, the safety, toler -Fig 1. a) Free-hand technique with US probe placed parallel to the femur neck; b) sagittal US showing synovium/capsule (long arrow), the needle situated in the articulation (three short arrows), and the femoral head (H); c) PRP ultrasound-guided IA injections ability and efficacy of PRP IA injections have been the subject of a preliminary report on 40 hip OA patients at 7 weeks' and 6 months' follow-up [18].…”
Section: Introductionmentioning
confidence: 99%